Transperitoneal Laparoscopic Repair of Retrocaval Ureter: Two Case Reports and A Review of Recent Literature - Sunder Goyal; Satya Parkash Yadav (Archives of Clinical and Experimental Surgery, 2013)
A retrocaval ureter is an unusual congenital anomaly that results in outer ureteral compression by the inferior vena cava. Open pyelopyelostomy or ureteroureterostomy procedures are done with good results. In the present era of minimal invasive access surgery, a laparoscopic technique is being used with the same good results with all advantages, like minimal analgesic, short hospital stay and with better cosmetic results. [Arch Clin Exp Surg 2013; 2(2.000): 116-123]